Analysis of Mortality Factors in COVID-19 Patients; Systematic Review - Yunita Liana; Pariyana; Mariana (International Journal of Science, Technology & Management, 2021)
Abstract. Coronavirus disease 2019 (COVID-19) is a highly contagious disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus. The increase in the number of COVID-19 cases is progressing quickly and has been spread between countries. As of October 14, 2020, there are 213 countries/regions around the world that have reported Covid-19 with a total of 38,002,699 confirmed cases of which 1,083,234 died. The purpose of this study was to determine the relationship between mortality factors and mortality in COVID-19 patients to predict the patient's prognosis. This research method is a systematic review through a literature review on mortality factors in COVID-19 patients Literature searches were accessed through internet searches using the Pubmed database based on the preferred reporting items for systemic review and meta-analysis (PRISMA). A systematic search was carried out on 18 October - 20 October 2020 with the keywords “COVID-19” AND “Death” OR “Decease” AND “Factor Associated”. There were 8 literature selected that met the inclusion and exclusion criteria. Based on the findings of the eight journals, mortality is old age, male, has a clinical condition of hypertension, obesity, diabetes, cardiovascular disease, lung disease, neurological disease, lymphophenia laboratory test results, hyperlactate dehydrogenase, increased procalcitonin, increased neutrophils, increased C-reactive protein, and increased D-dimer. All literature reported that a p value <0.05 was obtained from the analysis of the relationship between mortality factors and cases of death in COVID-19 patients. There is a significant relationship between mortality factors and the death of COVID-19 patients, where the mortality factors are elderly, male, have a clinical condition of hypertension, obesity, diabetes, cardiovascular disease, lung disease, neurological disease, lymphophenia laboratory test results, hyperlactate dehydrogenase, increase in procalcitonin, increase in neutrophils, increase in C-reactive protein, and increase in D-dimers in which the prognosis of patients who have mortality factors tends to be worse. Keywords: Mortality, Coronavirus, COVID-19